1998
DOI: 10.1007/s005350050191
|View full text |Cite
|
Sign up to set email alerts
|

A schwannoma of the cecum: Case report and review of Japanese schwannomas in the large intestine

Abstract: A 66-year-old Japanese man had a positive fecal occult blood test at a regular check-up, and a large polypoid mass was detected in the cecum by barium enema study. Colonoscopy showed a submucosal tumor with ulcer protruding into the cecal lumen. A large-forceps biopsy specimen was taken from the bottom of the ulcer. With the tentative diagnosis of neurogenic tumor, ileocecal resection was performed. The tumor showed spindle-cell proliferation in a concentric or fascicular pattern. Immunohistochemically, the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
1
24
0
2
Order By: Relevance
“…Discussion GI schwannomas are rare peripheral nerve sheath tumors that show a distinctive set of histologic features that differ from conventional central nervous system and peripheral, soft tissue schwannomas. These distinctive features include a peripheral lymphoid cuff, common microtrabecular pattern, and lack of nuclear palisading and xanthoma cells (Daimaru et al, 1988;Hirose et al, 1997;Miettinen et al, 2001;Prévot et al, 1999;Sarlomo-Rikala and Miettinen, 1995;Sasatomi et al, 2000;Scheithauer et al, 1999;Skopelitou et al, 1998;Tomozawa et al, 1998;Yagihashi et al, 1997). In this study, we evaluated NF2 and NF1 alterations in 20 well-documented GI schwannomas using archival formaldehyde-fixed, paraffinembedded (FFPE) material.…”
Section: Nf2 and Nf1 Status In Conventional Schwannomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion GI schwannomas are rare peripheral nerve sheath tumors that show a distinctive set of histologic features that differ from conventional central nervous system and peripheral, soft tissue schwannomas. These distinctive features include a peripheral lymphoid cuff, common microtrabecular pattern, and lack of nuclear palisading and xanthoma cells (Daimaru et al, 1988;Hirose et al, 1997;Miettinen et al, 2001;Prévot et al, 1999;Sarlomo-Rikala and Miettinen, 1995;Sasatomi et al, 2000;Scheithauer et al, 1999;Skopelitou et al, 1998;Tomozawa et al, 1998;Yagihashi et al, 1997). In this study, we evaluated NF2 and NF1 alterations in 20 well-documented GI schwannomas using archival formaldehyde-fixed, paraffinembedded (FFPE) material.…”
Section: Nf2 and Nf1 Status In Conventional Schwannomasmentioning
confidence: 99%
“…The tumor cells are positive for S-100 protein and glial fibrillary acidic protein (GFAP) and negative for desmin and ␣-smooth muscle actin (SMA), unlike true leiomyomas, and negative for KIT (CD117) and CD34, unlike GI stromal tumors. All tumors with such phenotypic features reported thus far have followed a benign clinical course (Daimaru et al, 1988;Hirose et al, 1997;Miettinen et al, 2001;Prévot et al, 1999;Sarlomo-Rikala and Miettinen, 1995;Sasatomi et al, 2000;Skopelitou et al, 1998;Tomozawa et al, 1998;Yagihashi et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous review of colonic schwannomas in Japan, only 4 of 41 cases (10%) were correctly diagnosed as schwannoma preoperatively (6). Preoperative imaging can be helpful to define the exact tumor location and obtain information about the tumor.…”
Section: Isolated Colonic Schwannoma In the Ascendingmentioning
confidence: 99%
“…It has been reported that perilesional lymphadenopathy are more often observed in gastric schwannomas than in gastric GIST (7). Although it is not certain, these lymph nodes are presumed to be reactive hyperplasia due to the fact that There are fourteen case reports of colonic schwannomas written in English or Korean and these reports provide accessible information about imaging findings (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We reviewed these cases as well as ours ( Table 1).…”
Section: Isolated Colonic Schwannoma In the Ascendingmentioning
confidence: 99%